2018
DOI: 10.1111/cob.12257
|View full text |Cite
|
Sign up to set email alerts
|

Impact of motivational interviewing on outcomes of an adolescent obesity treatment: results from the MI Values randomized controlled pilot trial

Abstract: The aim of this study is to examine outcomes from MI Values, a motivational interviewing (MI) intervention implemented adjunctive to obesity treatment. Adolescents (n = 99; 73% African American; 74% female; mean body mass index [BMI] percentile = 98.9 ± 1.2) were randomized to receive two MI sessions or education control. All adolescents participated in structured behavioural weight management treatment. Baseline, 3- and 6-month assessments of anthropometrics, dietary intake and physical activity were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 10 publications
0
44
0
2
Order By: Relevance
“…It is also possible to consider different options when deciding on the treatment mode of MI. Interventions that explored the outcomes of MI delivered by telephone demonstrated its effectiveness, 59 , 60 and the effect of home-based MI was not different from that of office-based intervention. 5 While MI-based text-messaging may not have a direct effect on decreased BMI, it may be a useful supplementary tool because it increases adherence to treatment and behavioral changes.…”
Section: Motivational Interviewingmentioning
confidence: 93%
“…It is also possible to consider different options when deciding on the treatment mode of MI. Interventions that explored the outcomes of MI delivered by telephone demonstrated its effectiveness, 59 , 60 and the effect of home-based MI was not different from that of office-based intervention. 5 While MI-based text-messaging may not have a direct effect on decreased BMI, it may be a useful supplementary tool because it increases adherence to treatment and behavioral changes.…”
Section: Motivational Interviewingmentioning
confidence: 93%
“…RCTs that reported TEI in kJ or kcal per day at each time point for intervention and control/comparison groups ( n = 29) were included in a meta‐analysis ( 26,31,35,46,61,68,70,73,78,80,83,89,95,106,108,116,120 ) . Results from the meta‐analyses showed that, compared to control groups, intervention groups achieved significantly greater reductions in mean total energy intake at ≤6 months (−194 kcal day −1 , 95% CI = −275.80 to −112.90 kcal day −1 , P < 0.001) and up to 12 months (−112 kcal day −1 , 95% CI = −218.92 to −5.83 kcal day −1 , P = 0.038) but not ≥12 months (19 kcal day −1 , 95% CI = −263.63 to 224.06, P = 0.87) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…RCTs that reported TEI in kJ or kcal per day at each time point for intervention and control/comparison groups (n = 29) were included in a meta-analysis (26,31,35,46,61,68,70,73,78,80,83,89,95,106,108,116,120) . Results from the meta-analyses showed that, compared to control groups, intervention groups achieved significantly greater reductions in mean total energy intake at (77) ITT analysis|Dietary adherence: Unannounced dietary recalls, NR|Dietary IV administrator: Dietitian|Diet: Dietary recalls (process measure)|Weight status: z-BMI, WC, %BF…”
Section: Meta-analyses Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 In another study, the use of MI is associated with reduction in energy intake, consistent with better adherence to dietitian visits. 45 Additionally, a study noted daily text messaging with MI can improve outcomes. 42 Behavioral medicine fits alongside the traditional medical treatment for obesity.…”
Section: Behavioral Therapiesmentioning
confidence: 99%